2019
DOI: 10.3390/antibiotics9010008
|View full text |Cite
|
Sign up to set email alerts
|

The Structure Features and Improving Effects of Polysaccharide from Astragalus membranaceus on Antibiotic-Associated Diarrhea

Abstract: Astragalus membranaceus (Astragalus) is often used as a medical and food resource in China. The present study was designed to investigate the features and effects of polysaccharide from Astragalus membranaceus (WAP) on rats with antibiotic-associated diarrhea (AAD). WAP was mainly composed of glucose, galactose, arabinose and glacturonic acid, with glucan, arabinogalactan and RG-I regions, and it showed loosely irregular sheet conformation. WAP decreased the inflammatory cell infiltration of colon in AAD rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Allobaculum cells are rod-shaped, stain Gram-positive and are arranged in pairs or chains ( 51 ). Related research showed that Allobaculum could produce butyric acid, and positively correlated with ANGPTL4 expression ( 52 , 53 ). Butyric acid could transactivate PPARγ and regulated ANGPTL4, the target gene of PPARγ, in colon cells ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Allobaculum cells are rod-shaped, stain Gram-positive and are arranged in pairs or chains ( 51 ). Related research showed that Allobaculum could produce butyric acid, and positively correlated with ANGPTL4 expression ( 52 , 53 ). Butyric acid could transactivate PPARγ and regulated ANGPTL4, the target gene of PPARγ, in colon cells ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there were 13 types of polysaccharides have β-D(1→6)-galactooligosaccharide branching β-D-(1→3)-galactose among the 14 types of polysaccharides isolated from Astragalus ( Kiyohara et al., 2010 ). Astragalus polysaccharide is the most important natural active component in Astragalus membranaceus, and exerts multiple pharmacologic effects ( Li et al., 2019 ). Recent studies have found that APS exerts multiple pharmacologic effects and strong extensive range of biological activities, including antioxidant, anti-inflammatory, antibacterial and antiviral, as well as profoundly affect the immune system ( Wang et al., 2016 ; Meng et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chinese yam can alleviate AAD symptoms by repairing the ampicillin-induced intestinal microbiota disorder, increasing the abundance of the intestinal probiotic Lactobacilli and Bifidobacteria , and decreasing the abundance of potential pathogenic Clostridium perfringens and Enterococcus [ 45 ]. Panax ginseng polysaccharides and Astragalus polysaccharides altered the diversity and composition of the gut microbiota in mice with AAD, induced by lincomycin hydrochloride, restored the gut microbiota, and promoted the metabolic balance and mucosal recovery [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This family is not only versatile with respect to complex carbohydrate degradation but is one of the stomach microbes involved in the expansion of type 2 innate lymphoid cells (ILC2s) that can produce secretory IgA (sIgA) to provide immune protection in the stomach [ 59 , 60 ]. In general, the modification effect of DESP on the intestinal flora is similar to other natural ingredients, including decreasing the number of harmful bacteria and increasing the relative abundance of Firmicutes , probiotics, and SCFA-producing bacteria, while improving the metabolic level and host immunity [ 45 , 46 , 61 ]. Furthermore, some natural active components, such as dietary polyphenols, can exhibit anti-diarrheal behavior by inactivating the LT produced by ETEC [ 62 ].…”
Section: Discussionmentioning
confidence: 99%